2019
DOI: 10.3390/nano9040491
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Conductive CNT Composites at Loadings below Theoretical Percolation Values

Abstract: It is well established that dramatic increases in conductivity occur upon the addition of conductive filler materials to highly resistive polymeric matrices in experimental settings. However, the mechanisms responsible for the observed behavior at low filler loadings, below theoretical percolation limits, of even high aspect ratio fillers such as carbon nanotubes (CNT) are not completely understood. In this study, conductive composites were fabricated using CNT bundles dispersed in epoxy resins at diverse load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
7
24
0
Order By: Relevance
“…Direct current (DC) and alternating current (AC) electrical testing of epoxy-CNT composites shows that electrically conductive levels, necessary for use in ESD and EMI applications, can be easily achieved. Remarkably, even at extremely low CNT loadings (<0.1 wt%), epoxy-CNT composites meet these conductivity values at ambient conditions [15,16,[19][20][21]. Prior observations indicate that the order of magnitude of the electrically conductive behavior, and the microstructure associated with such, are a function of CNT content; high to low loadings (>0.1 wt%) present connected CNT networks and resistivities in the order of~1 to 10 Ohm•cm, while extremely low CNT loading (<0.1 wt%) exhibit unconnected CNT strands and resistivities in the order of 10 2 to 10 4 Ohm•cm [15].…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Direct current (DC) and alternating current (AC) electrical testing of epoxy-CNT composites shows that electrically conductive levels, necessary for use in ESD and EMI applications, can be easily achieved. Remarkably, even at extremely low CNT loadings (<0.1 wt%), epoxy-CNT composites meet these conductivity values at ambient conditions [15,16,[19][20][21]. Prior observations indicate that the order of magnitude of the electrically conductive behavior, and the microstructure associated with such, are a function of CNT content; high to low loadings (>0.1 wt%) present connected CNT networks and resistivities in the order of~1 to 10 Ohm•cm, while extremely low CNT loading (<0.1 wt%) exhibit unconnected CNT strands and resistivities in the order of 10 2 to 10 4 Ohm•cm [15].…”
Section: Introductionmentioning
confidence: 82%
“…In previous work on DC measurements of epoxy-CNT composites, specifically EA9396 epoxy with Nancomp CNTs, it was clearly shown that resistivity values decreased as the concentration/loading of CNTs increased [15]. It was also reported that DC resistivity, as a function of current, is sensitive to CNT loading.…”
Section: Measurementsmentioning
confidence: 94%
See 3 more Smart Citations